Commercial photodiodes and phototransistors as dosimeters of photon beams for radiotherapy. Issue 9 (29th July 2021) - Ruiz‐García, Isidoro; Román‐Raya, Juan; Banqueri, Jesús; Palma, Alberto J.; Guirado, Damián; A. Carvajal, Miguel
Abstract : Purpose: The response to radiation typically used in radiotherapy treatments has been experimentally evaluated for three samples of two phototransistors (BPW85B and OP505A) and two PIN photodiodes types (VTB8440BH and BPW34S). Methods: To that end, a staggered irradiation cycle has been applied which included dose rate values from 0.81 to 4.87 cGy/s, achieving a total absorbed dose of 21.4 Gy. The samples have been irradiated with a linear accelerator and the relations between the induced photocurrent and the average and instantaneous dose rates, and between the accumulated charge and the absorbed dose, have been determined. The radiation‐induced output currents were measured by means of an external interface of the devices to a previously designed readout unit. Results: Experimental results of Si PIN photodiode BPW34S have shown a sensitivity of (13.9 ± 0.5) nC/cGy, slight sensitivity dependence on dose rate, and a high linearity of the current with the average and instantaneous dose rate, requiring only 10 V of reverse bias voltage. This device thermal drift has characterized and modeled for temperature effect compensation. Conclusions: Silicon PIN photodiode BPW34S, previously tested for X‐rays and Co‐60 gamma ray source, can also be a reliable candidate for dose rate and absorbed skin dose determination in typical radiotherapy treatments irradiations. A low sensitivity loss below 2% up to 21.4 Gy has been measured, allowing its use as an affordable reusable skin dosimeter. Moreover, no significant difference has been observed between its response to dose‐per‐pulse and changing pulse repetition frequency in terms of sensitivity and dependence with dose‐rate value.